The Acceptability of Tempeh Based Sausage Formulations with Natural Preservatives Addition - Sihite, Nathasa (JURNAL GIZI DAN KESEHATAN, 2021)
Sausage is a popular food for both children and adults. The main problem in sausage processing is their short shelf life. Synthetic preservatives such as nitrites are often added to sausage dough to extend the shelf life of sausages. Preservatives such as nitrites, if consumed too often can have harmful effects on health. The content of active compounds found in jasmine flowers is expected to be used as a source of natural preservatives in the processing of tempeh sausage in this study. This study aims to determine the acceptability of sausage formulations with the addition of natural preservatives. This study consisted of 3 treatments, namely tempeh sausage with extract variations of 0%, 0.1%, and 0.25%. This study used a completely randomized design (CRD). The concentration of jasmine flower extract had a significantly different effect on the taste of tempeh (p <0.05), where the higher the concentration of jasmine flower extract added to the tempeh sausage, the panelists' preference for the taste of the tempeh sausage would decrease. This is because the two basic ingredients of sausage, namely tempeh and jasmine flowers, already have a specific basic taste. The selection of preservatives made from natural ingredients can be a choice in developing food products, to minimize the use of synthetic preservatives in food products that are carcinogenic. Keywords: Sausage, tempeh, preservatives